The Honolulu Star-Advertiser, Weekly Eater column - Kam, Nadine (McClatchy - Tribune Business News, 2011)
[...] the staff would rather not share the menu, lest it spoil the surprise that accompanies any dramatic production. The ahi was presented plain with a side dipping sauce of shoyu with mountain potato, green onion, radish sprouts, slivered daikon and asparagus slices.